Linguistic Nationalism VS. Global Capitalism: The Fate of Bangla in the Changing Economy of Bangladesh - Hasan Shaikh; Muslima Akter (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Bangla, once the rallying cry of a nation’s liberation, now faces a quiet contest with English in the arenas of media, digital culture, and economic ambition. This paper investigates how linguistic nationalism is being reinvented under the pressures of global capitalism in present-day Bangladesh through a quantitative survey of 60 respondents. Statistical findings present an interesting duality: although Bangla is the first choice for traditional media, signage, and cultural heritage, English is being adopted as an inevitable gateway to international connectivity and economic opportunity. This tension demonstrates a population that is not letting go of its linguistic heritage but is strategically coping with a globalized world. The informants are concerned about the diminishing space for Bangla in digital entertainment and youth communication, but the majority is hopeful about the language’s survival. Although the study’s limited sample size and quantitative focus restrict generalizability, its findings shed light on a critical moment of linguistic transformation. It calls for forward-thinking language policies and digital innovation to ensure that Bangla remains not only remembered, but actively lived in a multilingual future.